Readiness Analysis for The Implementation of ISAK 335 in Financial Reporting at Universitas Gadjah Mada Academic Hospital (RSA UGM) - Rosady, Rina (Master in Accounting Program, 2025)
Universitas Gadjah Mada Academic Hospital (RSA UGM) is a special unit within a State University with Legal Entity (PTN-BH) authorized to manage its finances independently. In this context, preparing separate financial statements is essential for managerial accountability (stewardship) and to meet the information needs of external stakeholders (valuation), requiring compliance with applicable standards, particularly ISAK 335. This study aims to analyze RSA UGM’s readiness in financial reporting based on ISAK 335 and identify influencing factors. The research employed a descriptive qualitative case study method, with primary data obtained through in-depth interviews with four participants and secondary data from financial records and regulations. Results show that both external and internal regulatory pressures are the main drivers of ISAK 335 implementation. However, RSA UGM’s readiness remains partial, currently focusing on the Statement of Activities, Cash Flows, and Financial Position, while other components like the Statement of Changes in Net Assets and Notes to Financial Statements still require improvement, especially in financial systems and asset database accuracy. In conclusion, RSA UGM has demonstrated initial commitment but needs to strengthen internal regulations, enhance integrated information systems, and improve financial reporting processes to produce reliable, relevant, and decision-useful financial information.